Coordination of Inter-Agency Action for Nuclear Security in Uganda - Richard Sseggane (International Journal of Nuclear Security, 2020)
Despite the dynamic threats to the nuclear security of the East and Central African region, and the decision of the Government of Uganda to embark on a nuclear power programme, there was not much put in place as a coordination and cooperation mechanisms among the stakeholders in the nuclear security activities. This work confirmed the need in Uganda for the major nuclear security stakeholder agencies with roles and mandates for nuclear security including the regulator, security and intelligence agencies, police, border control, transport control, customs agencies and others to work together as necessary in the different nuclear security activities in order to strengthen the national nuclear security regime. In view of the findings of the researcher’s research thesis, and in line with international nuclear security legal framework, principles and IAEA guidance, recommendations are generated towards developing the most effective model for coordination of inter-agency action for nuclear security in Uganda.
Keywords: stakeholder cooperation and coordination in Nuclear security